2016
DOI: 10.1108/cg-05-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Board composition and corporate social responsibility in an emerging market

Abstract: Purpose The purpose of this paper is to examine the effect of board composition on corporate social responsibility (CSR) for selected Malaysian companies in Bursa Malaysia. Design/methodology/approach The paper analyses board composition and CSR of Malaysian (family and non-family) firms using linear regression analysis. Findings The empirical findings indicate that non-executive directors (NEDs) and independent non-executive directors (INEDs) designate a negative relationship, while women on board indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 77 publications
11
124
0
1
Order By: Relevance
“…This includes the disclosure of higher-quality information, which aids stakeholders to make better-informed decisions. With some exceptions (Amran et al, 2014;García-Sánchez, Cuadrado-Ballesteros, & Sepulveda, 2014;Sundarasen, Je-Yen, & Rajangam, 2016) and nuances found in this relationship (García-Sánchez & Martínez-Ferrero, 2017), previous empirical studies support a positive influence (Barako & Brown, 2008;Khan, 2010;Khan et al, 2013;Kilic et al, 2015;Lone & Khan, 2016;Rao et al, 2012). With some exceptions (Amran et al, 2014;García-Sánchez, Cuadrado-Ballesteros, & Sepulveda, 2014;Sundarasen, Je-Yen, & Rajangam, 2016) and nuances found in this relationship (García-Sánchez & Martínez-Ferrero, 2017), previous empirical studies support a positive influence (Barako & Brown, 2008;Khan, 2010;Khan et al, 2013;Kilic et al, 2015;Lone & Khan, 2016;Rao et al, 2012).…”
Section: Board Independence As a Determinant Of Csr Disclosurementioning
confidence: 87%
“…This includes the disclosure of higher-quality information, which aids stakeholders to make better-informed decisions. With some exceptions (Amran et al, 2014;García-Sánchez, Cuadrado-Ballesteros, & Sepulveda, 2014;Sundarasen, Je-Yen, & Rajangam, 2016) and nuances found in this relationship (García-Sánchez & Martínez-Ferrero, 2017), previous empirical studies support a positive influence (Barako & Brown, 2008;Khan, 2010;Khan et al, 2013;Kilic et al, 2015;Lone & Khan, 2016;Rao et al, 2012). With some exceptions (Amran et al, 2014;García-Sánchez, Cuadrado-Ballesteros, & Sepulveda, 2014;Sundarasen, Je-Yen, & Rajangam, 2016) and nuances found in this relationship (García-Sánchez & Martínez-Ferrero, 2017), previous empirical studies support a positive influence (Barako & Brown, 2008;Khan, 2010;Khan et al, 2013;Kilic et al, 2015;Lone & Khan, 2016;Rao et al, 2012).…”
Section: Board Independence As a Determinant Of Csr Disclosurementioning
confidence: 87%
“…Many papers focus on the influence of the adoption of different CG approaches on CSP [9][10][11][12][13][14]. However, these studies have not arrived at a consensus, and report contradictory and inconsistent results (e.g., while Cuadrado-Ballesteros et al [15] and Rao et al [16] found a positive connection, Sundarasen et al [17] and Walls et al [18] found a negative association, and Walls and Berrone [19] and Harjoto et al [20] found no significant relationship).…”
Section: Introductionmentioning
confidence: 85%
“…However, several studies find a negative connection between the independence of a company's board and CSP [17]. Hanniffa and Cook [14], Nurhayati et al [130], Walls et al [18] and Ortiz-de-Mandojana et al [130] all found that the presence of non-executive and independent directors on company boards has a negative influence on CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…Agency perspective is the most prominent theory used to examine the association between corporate governance, such as board attributes, and CSR reporting (e.g., Jain & Jamali, 2016;Sundarasen, Je-Yen, & Rajangam, 2016). The relationship between shareholders and managers triggers agency problems due to the information asymmetries between them (Jensen & Meckling, 1976).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In this regard, CEO duality might mitigate the effectiveness of the monitoring role of directors, may restrict the transparency to shareholders and all stakeholders (e.g., Giannarakis, 2014;Sundarasen et al, 2016), and may constrain the execution of certain governance roles, such as CSR disclosure. Consistent with agency theory, it is likely that managers' personal interests will affect their commitment to CSR practices and disclosure.…”
Section: Ceo Dualitymentioning
confidence: 99%